Research advances in functional roles of Th17 and IL-17 in acute kidney injury - Pang Hao-wen; An Ning; Yang Chen; Liu Hua-feng (Linchuang shenzangbing zazhi)
Acute kidney injury（AKI）is a clinical syndrome characterized by a rapid decline of renal function.Renal infiltrated immune cells and releases of inflammatory cytokines are key factors affecting the progression and outcome of AKI.Th17 cells and its inflammatory factors such as IL-17 are involved in immune regulation and mucosal defense and play key roles in autoimmune diseases.Recent studies have shown that Th17 cells and IL-17 not only affected the degree of kidney injury, but also modulated the recovery after AKI.This review summarized the latest research advances in the functional role of Th17 and IL-17 in AKI and discussed the therapeutic strategy by targeting Th17 cells and IL-17 in the treatment of AKI.